Land Pattern of Highly Urbanizing Cities: Change in Built-up Area, Population Density and Spatial Development of the Sprawling Dar es Salaam City. (March 2021) - Msuya, Ibrahim; Moshi, Irene; Levira, Francis
Dar es Salaam is one of the most diverse cities in Tanzania in terms of its physical, social, economic, environmental and spatial features. This diversity has contributed to differences in built-up area, population density, as well as the pace of spatial development across different parts of the city. This study aims to examine the relationship between physical built-up area changes in Dar es Salaam, population density change and spatial development using remote sensing images and census data. The study finds that the city population has grown tremendously, with peri-urban wards in particular having experienced positive growth. Dar es Salam's built-up area change and urban sprawl emerging at the city's edges distinctly follows the pattern of demographic change. This is accompanied by substantial compact growth in the inner parts of the city. A number of factors such as transport, residential development, migration, high natural growth rates, public policies and land speculation are found to have contributed to these changes. Overall, the study aims to aid planning authorities in effectively responding to the rapid spatial development taking place in the city, for which a holistic approach that combines an understanding of physical and demographic changes is needed. By investigating the changing patterns in land use within this highly urbanizing city, it aims to generate insights into urban development control machineries and identify their underlying dynamics.